2015
DOI: 10.3109/01480545.2015.1084631
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of gallic acid andSyzygium cuminiextract against oxidative stress-induced cellular injury in human lymphocytes

Abstract: ASc affects the purinergic system and may modulate adenosine levels, indicating that the extract of this plant exhibits immunomodulatory properties. ASc also may potentially prevent the cellular injury induced by oxidative stress, highlighting its cytoprotective effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 46 publications
1
13
0
1
Order By: Relevance
“…Antioxidant capacity of S. cumini leaf has been formerly shown for hydroethanolic [ 12 ] and aqueous [ 36 ] extracts, whereas PESc apparently present higher capacity. Both quercetin and gallic acid showed similar scavenging capacity of DPPH • compared to the extract, while myricetin presented higher IC 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Antioxidant capacity of S. cumini leaf has been formerly shown for hydroethanolic [ 12 ] and aqueous [ 36 ] extracts, whereas PESc apparently present higher capacity. Both quercetin and gallic acid showed similar scavenging capacity of DPPH • compared to the extract, while myricetin presented higher IC 50 .…”
Section: Discussionmentioning
confidence: 99%
“…All the changes can be caused by oxidative stress, such as cancer suppressor [23], cell normal functions [24], special responses for pathogens [25], maximal actions, and antigen presentation [26] (Figure 6). Pathway analysis revealed that, in intestinal mucosa tissues of participants from high altitude, many pathway genes had aberrant expression and may be also related with oxidative stress, especially in inflammatory bowel diseases [27, 28], myeloperoxidase [29], ROS production [10], apoptotic cell death [30], tissue damage [31], interleukin-1 [32], oxidative modification [33], cystic fibrosis [34], natural killer cells activity [35], lymphocytes [36], fibrinolysis [37] and so on (Figure 7). …”
Section: Resultsmentioning
confidence: 99%
“…The diversity and complexity of ellagic acid derivatives is actually determined on the type and amount of functional groups which can replace the hydroxyl groups either by methoxyl groups and the glycosyl groups mostly at position C-3, C-4, C-3' and C-4'. From here, for instance 3,3'-di-O-methylellagic acid (Reynertson, 2007) Simoes-Pires et al, 2009) has been isolated from S. cumini, beside ellagic acid its self (Simoes-Pires et al, 2009;De Bona et al, 2016). (Djoukeng, Mansour, Tapondjou, Lontsi & Tabacchi, 2007;Khan, Khan, Sahreen, & Ahmed, 2012).…”
Section: Resultsmentioning
confidence: 99%